Flexible Photodetectors: Flexible Light‐to‐Frequency Conversion Circuits Built with Si‐Based Frequency‐to‐Digital Converters via Complementary Photosensitive Ring Oscillators with p‐Type SWNT and n‐Type a‐IGZO Thin Film Transistors (Small 26/2021). Issue 26 (1st July 2021) - Jeong, Jinheon; Seo, Seung Gi; Yu, Seung‐Myeong; Kang, Yunha; Song, Junyoung; Jin, Sung Hun
Abstract : As a system‐level photodetector, flexible light‐to‐frequency conversion circuits (LFCs) are implemented using a‐IGZO and SWNT thin‐film transistors. Combined with LFC, CMOS‐based frequency‐to‐digital converter is integrated for digitization of analog signal from LFCs. With the better noise immunity on LFCs, the proposed system by Junyoung Song, Sung Hun Jin, and co‐workers (article number 2008131 ) will significantly contribute to the newly conceived Internet‐of‐Things (IoT) or smart flexible sensor systems.